Gender, Ideologi dan Kekuasaan dalam Video VICE Indonesia yang berjudul Polemik Poligami di Indonesia: Analisis Wacana Kritis Norman Fairclough - Isnaini Nur Azizah (Program Studi Sastra Indonesia, Fakultas Ilmu Budaya, Universitas Diponegoro, 2020)
Discourse is a part of communication that contains a though. The domination have a power to influence people to agree about the thoughs. Using the theory of Critical Discourse Analysis (CDA) by Norman Fairclough, this research reveals the domination of gender and the hidden ideology in video that uploaded by Vice Indonesia entitled” Polemik Poligami di Indonesia”. From the video, it can be seen that there is gender domination during the polygamy because women are not considere to do and have not the power to be fair. Thus, the ideology of patriarcky is clearly seen when the men have a power over their child and wife. Men are able to propagandize their family’s thoughs.